Suboptimal maternal nutrition, during early fetal liver development, promotes lipid accumulation in the liver of obese offspring - Melanie Healy (Reproduction, 2010)
Maternal nutrition during the period of early organ development can modulate the offspring's ability to metabolise excess fat as young adults when exposed to an obesogenic environment. This study examined the hypothesis that exposing offspring to nutrient restriction coincident with early hepatogenesis would result in endocrine and metabolic adaptations that subsequently lead to increased ectopic lipid accumulation within the liver. Pregnant sheep were fed either 50 or 100% of total metabolisable energy requirements from 30 to 80 days gestation and 100% thereafter. At weaning, offspring were made obese, and at ~1 year of age livers were sampled. Lipid infiltration and molecular indices of gluconeogenesis, lipid metabolism and mitochondrial function were measured. Although hepatic triglyceride accumulation was not affected by obesity per se, it was nearly doubled in obese offspring born to nutrient-restricted mothers. This adaptation was accompanied by elevated gene expression for peroxisome proliferator-activated receptor γ (PPARG) and its co-activator PGC1α, which may be indicative of changes in the rate of hepatic fatty acid oxidation. In contrast, maternal diet had no influence on the stimulatory effect of obesity on gene expression for a range of proteins involved in glucose metabolism and energy balance including glucokinase, glucocorticoid receptors and uncoupling protein 2. Similarly, although gene expressions for the insulin and IGF1 receptors were suppressed by obesity they were not influenced by the prenatal nutritional environment. In conclusion, excess hepatic lipid accumulation with juvenile obesity is promoted by suboptimal nutrition coincident with early development of the fetal liver.